Sexually transmitted diseases still an existing problem - Puszkarz, Irena (Journal of Education, Health and Sport, 2017)
Increasing number of cases of STD is an alarming issue. It is a cause of serious health consequences within society and concern for public health. According to WHO 2/3 of STD affect young people (around 20 years old). The aim of the study is examine the epidemiological situation with selected STD in Poland in 2015. The study has been based on literature and data related to incidence of syphilis, gonorrhoea, chlamydia, HIV and HPV infections. The data has been obtained from the National Institute of Public Health – National Institute of Hygiene, National AIDS Centrum and National Oncology Register. In 2015 within Poland there have been 1338 incidences of early and late syphilis, on average 3.22 per 1 thousand people. The incidence of congenital syphilis has decreased from 20 cases in 2014 to 12 in 2015. There have been 441 incidences of gonorrhoea (on average 1.15/100 000). In 2015, 1295 people were diagnosed with HIV, 134 incidences of AIDS have been reported, 40 patients died. There were 220 cases of infections (0.57/100000) caused by chlamydia. Every year in Poland there are 4000 cases of malignant cervical cancer (4%) and 2400 of deaths because of cervical cancer. The epidemiological situation is affected by the lack of preventive and educational actions, low awareness of health within society and easy access to sex services. The National plan to fight STD should have a social character and it should ensure that there are sufficient funds necessary to conduct preventive and educational programs.